2014
DOI: 10.2147/ijn.s73010
|View full text |Cite
|
Sign up to set email alerts
|

Follicular delivery of spironolactone via nanostructured lipid carriers for management of alopecia

Abstract: Spironolactone (SL) is a US Food and Drug Administration-approved drug for the treatment of hypertension and various edematous conditions. SL has gained a lot of attention for treating androgenic alopecia due to its potent antiandrogenic properties. Recently, there has been growing interest for follicular targeting of drug molecules for treatment of hair and scalp disorders using nanocolloidal lipid-based delivery systems to minimize unnecessary systemic side effects associated with oral drug administration. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 48 publications
4
57
0
Order By: Relevance
“…One drop of dispersion was deposited on the surface of a carbon-coated copper grid and left to adhere on the carbon substrate for 1 min and any excess of dispersion was removed by a tip of filter paper (Tavano et al, 2013;Shamma & Aburahma, 2014).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 1 more Smart Citation
“…One drop of dispersion was deposited on the surface of a carbon-coated copper grid and left to adhere on the carbon substrate for 1 min and any excess of dispersion was removed by a tip of filter paper (Tavano et al, 2013;Shamma & Aburahma, 2014).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…ZT, Span Õ 80, stearic acid, cholesterol and lyophilized ZT loaded novasomes were subjected to DSC (PerkinElmer, Waltham, MA). Approximately 4 mg of samples were analyzed in sealed aluminum pans in the temperature range from 30 to 300 C at a heating rate of 10 C/min under inert nitrogen flow (25 mL/min) (Shamma & Aburahma, 2014).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Clinical studies with alcoholic topical formulation of SP have been previously reported and the results demonstrate beneficial effects in patients with acne without any systemic hormonal changes [3,12,13]. Shamma and Aburahma used spironolactone loaded NLC for follicular targeting of drug molecules for the management of alopecia and they successfully showed the presence of SP in the scalp hair follicles and decreasing androgen production within sebaceous glands and blocking the androgen receptor in dermal papillae [14]. The efficacy of SP gel 5% in the treatment of facial acne also showed that total lesion count and acne severity index reduced significantly however, efficacy on non-inflammatory lesion (comedones) was more effective than on inflammatory ones (papules and pustules) because of poor ability of SP penetration to specific micro environmental conditions in the inflammatory acne lesions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a nanocosmeceutical-based approach of promoting hair growth was achieved using delivery technologies, such as niosomes and liposomes, to hair follicular cells. [106][107][108][109][110][111][112][113] Curcumin-based liposomes were constructed and had 70% enhanced penetration of the curcumin to the hair growth, irrespective of liposomes type in the size range of 213-320 nm. 114 Similarly, a curcumin-based cyclodextrin complex also showed enhanced follicle penetration and hair growth enhancement.…”
Section: Nanosunscreensmentioning
confidence: 99%